Perlindungan Hukum Terhadap Pengembang Atas Wanprestasi Konsumen Dalam Perjanjian Jual Beli Rumah Secara In House - Sarahalfaroq99 Muhammad Sarah Al Faroq (Yayasan Baitul Hikmah al-Zain, 2024)
House is a fundamental necessity that is crucial for every individual. Houses can be acquired by either constructing them oneself or purchasing from a Development Company. The method of purchasing a house can be through credit from a bank or direct installment to the developer without involving third parties (in-house). The in-house scheme is currently more preferred by buyers because the process is uncomplicated, the principal payment is interest-free, and the installment period can be arranged according to mutual agreement. Every legal entity engaging in a sale and purchase agreement requires legal protection guaranteed by the State to ensure legal certainty. This is exemplified by the enactment of Law Number 8 of 1999 concerning Consumer Protection (Consumer Protection Law). The background for the establishment of the Consumer Protection Law is the perceived vulnerability of consumers compared to business entities. However, it is a fact that businesses can also suffer from the breach of contract by consumers. The Consumer Protection Law only elaborates on legal protection for consumers and does not specifically outline the legal protection provided to businesses